Pengaruh Penerimaan Dana ZISWAF, NPF Gross, dan Pendapatan Mudharabah terhadap BOPO dengan Firm Size sebagai Variabel Moderasi Periode Tahun 2018.Q1 – Tahun 2023.Q3 - Putri, Rahmaniyah Indria; Hestya Budianto, Eka Wahyu (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2024)
This research aims to determine the effect of ZISWAF Fund Revenue, Gross NPF, and Mudharabah Income on BOPO with Firm Size as a Moderating Variable. The samples used in this study are companies in the financial sector listed on the Indonesia Stock Exchange (BEI) in 2018Q1-2023Q3. The sampling technique used was purposive sampling, with a total sample of 115 from 5 (five) Islamic banks. The data analysis technique used is Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results showed that the receipt of ziswaf funds had a significant negative effect on BOPO in the financial sector for the 2018Q1-2023Q3 period. Gross NPF has a positive effect on BOPO in the financial sector for the period 2018Q1-2023Q3. Mudharabah income has a significant negative effect on BOPO in the financial sector for the period 2018Q1-2023Q3. Firm size is not able to moderate the effect of ziswaf fund revenue on BOPO in the financial sector for the period 2018Q1-2023Q3. Firm size is unable to moderate the effect of Gross NPF on BOPO in the financial sector for the period 2018Q1-2023Q3. Firm size is able to moderate the effect of mudharabah income on BOPO in the financial sector for the period 2018Q1-2023Q3.